Inhibition of peptidoglycan biosynthesis in gram-positive bacteria by LY146032. - Allen, N E (1987)
LY146032, a cyclic lipopeptide antibiotic, is an inhibitor of cell wall peptidoglycan biosynthesis in gram-positive bacteria. Although LY146032 at relatively high concentrations inhibited the in vitro polymerization of UDP-linked sugar precursors, inhibition of cell wall formation in intact Staphylococcus aureus and Bacillus megaterium cells did not lead to the accumulation of UDP-N-acetyl-muramyl (MurNAc)-peptide(s). Experiments that measured formation of UDP-MurNAc-peptides revealed that LY146032 inhibited the formation of these nucleotide-linked intermediates. This antibiotic had a disruptive effect on membrane permeability as evidenced by the loss of intracellular potassium immediately after exposure to the drug. The lack of any major disruption of the phosphoenolpyruvate:sugar phosphotransferase system indicated that the membrane is not likely a lethal target for this antibiotic. The findings are consistent with a mechanism by which LY146032 inhibits the formation of precursor molecules utilized in peptidoglycan biosynthesis. The observed membrane effects likely result from transit of the inhibitor to its lethal target site.